Conservation of indigenous vegetables in the Philippines: A scoping study - Oraye, Claudette D.; de Chavez, Hidelisa D.; Aguilar, Catherine Hazel M.; Makiling, Florisa C.; Ladia, Villamor A. Jr.; Enicola, Elmer E.; Maghirang, Rodel G.; Anunciado, Ma. Shiela; Monville-Oro, Emilita; Gonsalves, Julian; Hunter, Danny; Borelli, Teresa; et al. (2023)
Seasonality and inconsistent vegetable supplies due to the impacts of climate change (i.e., varying rainfall patterns and drought), are major factors contributing to the availability and affordability of vegetables. There is a need to increase access to a diverse range of high-quality, resilient, and nutritious species and cultivars that are aligned to consumer and farmers’ preferences. In addition, crop diversification can address the challenges brought on by seasonality, improve dietary diversity for better nutrition, and strengthen environmental resilience. There is growing interest in the Philippines on the promotion of indigenous vegetables (IVs) for food security and nutrition. IVs play a crucial role in food security, income generation, and food culture. Their adaptability, plasticity, and resilience to biotic and abiotic stresses provide farmers with the needed coping strategies to confront climate change.